Analisis Kemampuan Literasi Sains Siswa SMP pada Materi Sirkulasi Darah - Siti Hardiyanti Hasasiyah; Bagus Addin Hutomo; Bambang Subali; Putut Marwoto (Jurnal Penelitian Pendidikan IPA, 2020)
Science literacy is the ability to use scientific knowledge to identify questions, explain scientific phenomena that occur using contextual facts. The circulation theme is one of the themes of contextual learning that is very closely related to everyday life. This study aims to determine the scientific literacy skills of students in blood circulation material at the junior high school level. The research method used was descriptive qualitative with scientific literacy instruments in the form of tests with research subjects 38 students of SMP N 4 Belik class VIIID academic year 2018/2019. The results of this study indicate that students' literacy skills in the category are low. This can be seen from the aspect of identifying valid scientific opinions (58%), understanding the design elements of the research findings (24%), being able to solve questions based on scientific phenomena (32%), understanding and interpreting basic statistics (21%) and students able to make inferences, predictions, and draw conclusions based on data (39%). The value obtained by students is divided into four categories of values obtained by students, which are very low, low, sufficient, and high based on the results of research, the average literacy skills of students in the low category. The conclusion of this study is that the science literacy skills of junior high school students are low on aspects of understanding and interpreting basic statistics. Keywords: Science Literacy, Contextual, Blood Circulation